TINJAUAN YURIDIS PERTANGUGNJAWABAN PRESIDEN DALAM PELAKSANAAN HAK KONSTITUSIONAL SESUDAH AMANDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Meydianto Mene (Ensiklopedia Social Review, 2020)
In the Constitution of the Republic of Indonesia Year 1945 stipulates that Indonesia is adopting a presidential system in the administration of the State. The consequence of this system, as stipulated in Article 4, paragraph 1 of the 1945 Constitution, that the president acts as head of government. In addition, implied by reference in Article 10 to Article 15 of the 1945 Constitution, the president also acted as Head of State, of the provisions of the president has a great power. In the 1945 Constitution besides regulating the system of government also regulates the powers of the president who is usually known as the Right Prerogative but the authors have called for Constitutional Rights. Authorizations are set out in Articles 10, 11, 12, 13, 14 and Article 15 of the 1945 Constitution existence of the special session is not mentioned explicitly in the 1945 Constitution Article 2 paragraph (2) of the 1945 Constitution states that the Assembly convene at least once in five years, however Tap. III / 1978 set for the existence of the special session (SI) to hold the president in the middle of his term.